Implementation of flipped ESL classroom at two private tertiary education institutions / Marina Mohamad Amir - Marina , Mohamad Amir (2021)
Flipped classroom model is a pedagogical strategy which utilises technology to move the lecture outside of the classroom, thus giving more time in the classroom for students to work cooperatively with their peers. It is even mentioned as one of the important developments in educational technology for higher education. However, only a few studies done in showing that the implementation of this model achieved favorable outcome in Malaysian tertiary ESL classrooms. It is because the elements of FC are misunderstood by the lecturers and the students. Besides, previous studies showed that the concept and design of this model was under-utilised in the tertiary education ESL classroom. Thus, this study aims to explore the implementation of this model in ESL classrooms at two private tertiary education institutions as well as to investigate the lecturers’ and students’ perceptions in conducting the lessons. In order to achieve this aim, this study has conducted a qualitative study which includes classroom observations and semi-structured interviews with the lecturers and the students. The findings showed that there are six strategies that have been implemented which are preparation of online learning content, the use of interactive platforms, a check for students’ understanding of the content, reinforcements for students to prepare prior class, iteration of online learning content and arrangement of engaging in-class activities. The lecturers perceived this model enhanced their teaching and students’ learning. In addition, the students also perceived that they prefer this model than the traditional classroom. Nonetheless, they still faced challenges while conducting flipped classroom model. As a result, ESL instructors who are interested in implementing this model should fully understand its elements and consider the challenges so that this model can be implemented successfully and reap its benefits.